Logos der Vernunft - Logos des Glaubens - Prostmeier, Ferdinand R.; Lona, Horacio E. (Millennium-Studien / Millennium Studies, 2010)
The terms ´logos of reason` and ´logos of belief` refer to two important aspects of western culture at the beginning of the Christian era. On the one hand there is the classical tradition, with its comprehensive claim to be able to explain the truth about reality by means of the logos. On the other hand there is the Christian message, which proclaims the self-revelation of God in the form of the Son, and so also claims for itself the truth about God, mankind and the world. The semantic ambiguity of the term ´logos` provided the occasion for a controversy that unfolded among the educated. The contributions to this volume present aspects of the controversy, and attempt to illuminate the connection between culture, belief and transmission against its historical background.